Literature Study of The Implementation of Skimming Techniques in Improving Quick Reading Ability in Indonesian Language Students in Class V: Studi Pustaka Penerapan Teknik Skimming Dalam Meningkatkan Kemampuan Membaca Cepat Pada Siswa Bahasa Indonesia Kelas V - Dien Rufaida; Kemil Wachidah (Academia Open, 2022)
This study was to describe the process of skimming techniques for elementary school students to improve reading skills. This study used a literature study approach using the Systematic Literature Review (SLR) method. The journal subject comes from Google Scholar with research limitations of elementary school students that have been analyzed by the researcher. The results of Eve's research show that there is an increase in reading skills in Indonesian language lessons for students. This can be seen from the first and second cycles of active students, educators and student learning outcomes. The first cycle the total value of the student's activeness observation, with a score of 62.5% with a sufficient predicate. Whereas in the second cycle the number of scores obtained on student learning activeness got a score of 87.5% with the predicate good and very good. The results of Muhtar's research stated that after the paired t-test analysis was carried out, it was found that there was an effect of the application of the skimming technique on students' reading ability. Five to determine the level of student ability. After adjusting for the five scale score interval, it is known that the score is 95.25%, therefore this score is included in the Very Good category. This can be proven that the ability of students when reading fast using skimming techniques is included in the excellent category during the speed reading test and in understanding the content of the text reading. From the results of analyzing the research that has been done previously carried out by Hawa, Muhtar, and Fitria that Skimming techniques can help students' ability to read quickly in Indonesian lessons.